Assessing the use of supplementary materials to improve genomic variant discovery. (31st March 2023) - Pasche, Emilie; Mottaz, Anaïs; Gobeill, Julien; Michel, Pierre-André; Caucheteur, Déborah; Naderi, Nona; Ruch, Patrick
Abstract: The curation of genomic variants requires collecting evidence not only in variant knowledge bases but also in the literature. However, some variants result in no match when searched in the scientific literature. Indeed, it has been reported that a significant subset of information related to genomic variants are not reported in the full text, but only in the supplementary materials associated with a publication. In the study, we present an evaluation of the use of supplementary data (SD) to improve the retrieval of relevant scientific publications for variant curation. Our experiments show that searching SD enables to significantly increase the volume of documents retrieved for a variant, thus reducing by ∼63% the number of variants for which no match is found in the scientific literature. SD thus represent a paramount source of information for curating variants of unknown significance and should receive more attention by global research infrastructures, which maintain literature search engines . Database URL https://www.expasy.org/resources/variomes